PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Divisi Finishing CV Laksana Ungaran) - Evayanti, Shela; Waloejo, Handoyo Djoko (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
CV Laksana is a company engaged in the bus-making car body industry, located in Ungaran. The competition of the car body industry in Indonesia has begun to increase, so we need human resources who have high quality work. The performance evaluation of CVLaksana employees includes competence, work performance, cooperation, communication, loyalty, and initiative. This study aims to determine the effect of organizational culture and compensation on employee performance (Study of Employees in the finishing division of CV Laksana Ungaran). This type of research is explanatory research. The sampling technique uses systematic random sampling technique. The number of samples taken was 75 respondents, who were finishing division employees. Research used to determine the effect of organizational culture and compensation on employee performance using statistics with the help of the IBM SPSS version 21.0 system The results showed that organizational culture affected employee performance by contributing 21%, compensation affected employee performance by contributing 18.9%, and simultaneously organizational culture and compensation affected employee performance contributing 28.7%. While the rest is influenced by factors other than organizational culture and compensation. Based on the calculation of the F Test shows that there is a significant influence between organizational culture and compensation on employee performance. Suggestions for improving employee performance in this study are the need to check the employee's work related to employee accuracy and orientation towards work results. Policy making should management consider the policy to be taken in order to have a positive impact on employees. The company need to socialization about the culture in CV Laksana namely 5R and Sat Dharma Laksana so that employees can be obeyed and implemented. In providing compensation, the company should consider based on input from several employees regarding the amount of salary, incentives, and benefits so that the range of salary, incentives, and benefits obtained as expected by the employee is obtained.